1975
DOI: 10.1149/1.2134425
|View full text |Cite
|
Sign up to set email alerts
|

Electrode Kinetics of Antimony in Acidic Chloride Solutions

Abstract: The kinetics of the electrode processes of antimony in normalKCl‐normalHCl solutions have been investigated. The rest potential of antimony in acidic chloride solutions can be expressed empirically by the equationEnormale=0.182−0.060 pH+0.020log][normalSb)(IIIand is attributed to the redox reactionnormalSb+2H2O=HSbO2+3H++3eThe empirical rate equations for the electrodissolution and electroreduction reactions near the rest potential areInormala=k̅normala][OH−SbIII−1e2FE/RTandInormalc=k̅normalcH+2e−FE/RTThe ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…For polycrystal Sb in HCl-KCl solutions the electrodissolution rate was first order with respect to both hydroxyl ion and Sb(111) concentrations, and the electrodeposition rate of Sb(III) was first order with respect to both H + and Sb(III) concentrations. 6 In the present study, Sb in 0.1M HClO 4 -NaOH solutions, the corrosion potential was linearly dependent on pH but the corrosion rate was approximately independent of pH.…”
Section: Resultsmentioning
confidence: 41%
See 1 more Smart Citation
“…For polycrystal Sb in HCl-KCl solutions the electrodissolution rate was first order with respect to both hydroxyl ion and Sb(111) concentrations, and the electrodeposition rate of Sb(III) was first order with respect to both H + and Sb(III) concentrations. 6 In the present study, Sb in 0.1M HClO 4 -NaOH solutions, the corrosion potential was linearly dependent on pH but the corrosion rate was approximately independent of pH.…”
Section: Resultsmentioning
confidence: 41%
“…5 Further, polycrystalline Sb in acidic chloride solutions has been studied. 6 There were considerable differences in the corrosion characteristics of the InSb's (111)-In and (111)-Sb surfaces. For the Sb in acidic chloride solutions an empirical rate expression for Sb has been obtained and an electrodissolution mechanism has been proposed based on the experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the question cannot be answered unequivocally. Studies of the electrochemistry of antimony reported in the literature do not provide an answer (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Superposition of the cathodic polarization curves for tin (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There were considerable differences in the corrosion characteristics of the InSb (111)-In and (111)-Sb surfaces. Polycrystalline and monocrystalline Sb in aqueous solutions had been studied, and the results published including an extensive literature of previous work (6). For Sb in acidic chloride solutions an empirical rate expression for Sb had been obtained and an electrodissolution mechanism proposed based on the experiments (6).…”
Section: Introductionmentioning
confidence: 99%
“…Polycrystalline and monocrystalline Sb in aqueous solutions had been studied, and the results published including an extensive literature of previous work (6). For Sb in acidic chloride solutions an empirical rate expression for Sb had been obtained and an electrodissolution mechanism proposed based on the experiments (6). Further, indium electrodissolution in aqueous solutions has been reported (see also references therein) (7).…”
Section: Introductionmentioning
confidence: 99%